South Africa : Report on the Observance of Standards and Codes on Banking Supervision, Insurance Supervision, and Securities' Regulation. (IMF Staff Country Reports; Country Report ;, 2010)
In South Africa, long-term insurers experienced some strains during the financial crisis, but there were no crisis-related failures. The capital markets suffered sharp declines but no systemic failures. The three standards assessments have found the regulatory system fundamentally sound. The National Treasury has authority to set and oversee national regulatory policy. Banking supervision is effective and has contributed to reducing the impact on the financial sector of the global financial crisis. Insurance regulation is sound and while the assessment identifies areas for development, these are being addressed.